Hydrocarbon steam reforming using Silicalite‐1 zeolite encapsulated Ni‐based catalyst. Issue 1 (10th October 2016) - Cimenler, Ummuhan; Joseph, Babu; Kuhn, John N.
Abstract : A Silicalite‐1 zeolite membrane encapsulated 1.6 wt % Ni–1.2 wt % Mg/Ce0.6 Zr0.4 O2 steam reforming composite catalyst synthesized by a physical coating method was used to investigate effect of encapsulation on size selective steam reforming, using methane (CH4 ) and toluene (C7 H8 ) as representative species. Characterization methods (scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), Physisorption Analysis, and x‐ray diffraction (XRD)) were used to analyze pre‐ and post‐reaction samples. SEM, EDS, and XRD analyses showed that Silicalite‐1 was coated successfully onto the core catalyst. Weisz‐Prater Criteria and Thiele moduli calculations indicated internal diffusion limitations. Combined reforming of CH4 and C7 H8 at 800°C on the composite catalyst demonstrated stability during the 10 h time on stream while the uncoated SR catalyst deactivated. The non‐acidic Silicalite‐1 encapsulated catalyst showed decreases (∼2–7%) in both CH4 and C7 H8 conversions compared to acidic H‐β zeolite confirming that shell acidity did contribute to conversion and suggested that shell defects/grain boundaries were responsible for the C7 H8 conversion. © 2016 American Institute of Chemical Engineers AIChE J, 63: 200–207, 2017